Validating a Structural Model of Destination Image, Satisfaction, and Loyalty Across Gender and Age - Assaker, Guy (2015)
This study validates an interesting model of destination image (DI), tourist satisfaction, and loyalty across gender and age. We confirm that DI predicts satisfaction and has a significant direct and indirect effect on loyalty. After examining the validated structural model across different groups of respondents based on gender, age, and the gender by age interaction, we found that the model constructs differ across some of the groups. Specifically, young males from the sample were less likely to develop destination loyalty despite having a strong destination image of Australia and reportedly being satisfied with their trip experience. The findings present important implications concerning the predictors of destination loyalty across market segments with different demographics.